Adrenergic effects on secretion of epidermal growth factor from Brunner's glands. Issue 9 (September 1985) - Olsen, P S; Poulsen, S S; Kirkegaard, P
Abstract : The influence of the sympathetic nervous system and adrenergic agonists on flow rate and secretion of epidermal growth factor (EGF) from Brunner's glands has been investigated in the rat. Chemical sympathectomy by administration of 6-hydroxydopamine increased volume secretion and output of EGF from Brunner's glands but depleted the glands of EGF. Infusion of noradrenaline, an alpha-adrenergic agonist, inhibited basal and vasoactive intestinal polypeptide (VIP) stimulated flow rate and output of EGF from Brunner's glands and increased the amount of EGF in the tissue. Vasoactive intestinal polypeptide also increased the amount of EGF in Brunner's gland tissue and this was unchanged after simultaneous infusion of VIP and noradrenaline as well as VIP and isoproterenol, a beta-adrenergic agonist. Isoproterenol had no effect on basal and VIP stimulated secretion of EGF from Brunner's glands. The presence of PAS-positive mucus in Brunner's glands was unchanged during infusion of noradrenaline whereas VIP induced a depletion of Brunner's gland mucus which in turn was prevented by simultaneous infusion of noradrenaline. This study indicates that the sympathetic nervous system influence the volume secretion, output of EGF and mucus content in Brunner's glands probably by activation of alpha-adrenergic pathways.